2007
DOI: 10.1175/jcli3985.1
|View full text |Cite
|
Sign up to set email alerts
|

Amazon and Orinoco River Plumes and NBC Rings: Bystanders or Participants in Hurricane Events?

Abstract: ABTRACTThe Amazon and Orinoco River plumes and North Brazil Current (NBC) rings are investigated during the 1 June through 30 November Atlantic hurricane season to identify their impact on upper-ocean temperatures in the region and to draw attention to their potential role in hurricane maintenance and intensification. The analysis uses ocean temperature and salinity stratification data, infrared and microwave satellite-derived sea surface temperature (SST) data, and Atlantic tropical storm and hurricane tracks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 43 publications
8
105
0
2
Order By: Relevance
“…Past studies have suggested a potential role of BLs in TC-induced SST cooling (19) and TC intensification (20)(21)(22). However, the impact of BLs on TC intensification has not been definitively demonstrated or quantified.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Past studies have suggested a potential role of BLs in TC-induced SST cooling (19) and TC intensification (20)(21)(22). However, the impact of BLs on TC intensification has not been definitively demonstrated or quantified.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As the BL plays a role in trapping the heat within the upper ocean layer, it may also affect the Atlantic hurricane activity (Ffield, 2007;Vizy and Cook, 2009). The Amazon plume, which extends into the Caribbean Sea, has relatively high SSTs.…”
Section: Introductionmentioning
confidence: 99%
“…Este último influi na distribuição de salinidade nas águas tropicais e, de forma indireta, na variabilidade das propriedades termodinâmicas em larga extensão sobre o oceano Atlântico tropical. Influencia também no estoque de nutrientes na plataforma continental, porém algumas evidências quantitativas de águas amazônicas reconhecem o relativo suprimento de nutrientes a partir do rio e também de fontes advectivas (Gibbs, 1972;Milliman e Boyle, 1975;Sprintall e Tomczac, 1992;Pailler et al, 1999;Silva et al, 2005a,b;Silva et al, 2007a,b;Ffield, 2007;Subramaniam et al, 2008). Calef e Grice (1967) mostram que as lentes de águas amazônicas afetam a diversidade e a quantidade de certas comunidades planctônicas ao largo da foz do rio Amazonas.…”
Section: Introductionunclassified